Construction of Tn5 lac, a transposon that fuses lacZ expression to exogenous promoters, and its introduction into Myxococcus xanthus. - Kroos, L (1984)
A promoterless trp-lac fusion fragment was inserted near one end of the bacterial transposon Tn5 in the correct orientation to fuse lacZ gene expression to promoters outside Tn5. The resulting transposon, Tn5 lac, retains the kanamycin-resistance gene of Tn5 and transposes in Escherichia coli at 6% the frequency of Tn5 to many different sites in a bacteriophage lambda target. Expression of beta-galactosidase, the product of the lacZ gene, from Tn5 lac insertions in phage lambda depends both on insertion into a transcription unit in the correct orientation and on the regulation of the promoter of the transcription unit, verifying that by transposition Tn5 lac can fuse lacZ expression to outside promoters. An insertion of Tn5 lac in bacteriophage P1 was isolated and used to introduce Tn5 lac into Myxococcus xanthus, a bacterium that undergoes multicellular development. Stable kanamycin-resistant transductants are obtained that contain no P1 DNA sequences but have Tn5 lac inserted at different sites in the Myxococcus chromosome. Individual transductants express different levels of beta-galactosidase. A chromogenic substrate of beta-galactosidase, 5-bromo-4-chloro-3-indolyl beta-D-galactoside, is toxic in Myxococcus when cleaved in large amounts. In principle, Tn5 lac could be used to assay transcription in any bacterium in which Tn5 can transpose and beta-galactosidase can be measured.